Examining Full Collateral Coverage in Canada's Large Value Transfer System - Lana Embree; Varya Taylor (Bank of Canada, 2015)
The Large Value Transfer System (LVTS) is Canada's main electronic interbank funds transfer system that financial institutions use daily to transmit thousands of payments worth several billions of dollars. The LVTS is different than real-time gross settlement (RTGS) systems because, while each payment is final and irrevocable, settlement occurs on a multilateral net basis at the end of the day. Furthermore, LVTS payments are secured by a collateral pool that mutualizes losses across participants in the event of a default. In this paper, we use the Bank of Finland Simulator to examine the implications of fully collateralizing LVTS payments, similar to an RTGS. An important caveat to consider, however, is that the simulations do not take into account the anticipated change in payment behaviour in response to a change in collateral requirements. In this regard, we include a queuing mechanism to at least reflect more efficient use of liquidity. The results indicate that collateral requirements vary by participant and some participants actually require less collateral in the simulation than what is required under the current LVTS design.
Keywords: E4; E47; G2; G21; 330; Financial institutions; Payment clearing and settlement systems